PENGARUH IKLAN DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG SERI GALAXY (SURVEI PADA PELANGGAN ITC ROXY MAS) - Saidani, Basrah; Ramadhan, Dwi Raga (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2013)
Generally, the purpose of this research are: 1) to get more knowledge about Advertising, product attributes and the decision to purchase smartphone Samsung Galaxy series,. 2) to get more knowledge about the influenace of Advertising to purchasing decisions smartphone Samsung Galaxy series, 3) to get more knowledge about the influence of product attributes to purchasing decisions smartphone Samsung Galaxy series, 4) to get more knowledge about influenace of Advertising and product attributes simultaneously the decision to purchase smartphone Samsung Galaxy series. The observation unit in this research is 100 respondents visitors ITC Roxy Mas – Jakarta to purchase smartphone Samsung Galaxy series. Technique of determining the sample using a convenience sampling technique. Data collection techniques using the questionnaire Likert scale from 1 to 5. Descriptive analysis results showed: 1) the Advertising from Samsung Galaxy series is good enough as a whole but still lacking in message Acceptance and message retention. 2) Attribute a good product overall dimesi dominated by product fitures, 3) the decision to purchase is dominated by post-purchase where consumers get satisfaction after buying the Samsung Galaxy series. Hypothesis testing results showed: 1) Advertising have a significant effect on purchasing decisions, 2) product attributes have a significant effect on purchasing decisions, 3) Advertising and product attributes a significant effect on purchasing decisions. Key words: Advertising,, Product Attributes, and Purchase Decision